A Comparative Analysis of Barriers and Enablers to Men and Women’s Use and (Non) Adoption of Mechanization Technology from East and Southern Africa - Enokenwa Baa, Ojong; Davis, Kristin E.; Ngoma, Hambulo; Simutowe, Esau (International Water Management Institute, 2023)
Countries in East and Southern Africa face multiple challenges, including climate change impact, in addition to other crises such as land degradation, poor yields, food and nutrition insecurity, resource scarcity, ecosystem and biodiversity loss, and rapid population growth (Diaz et al. 2019). While these interact, the extent to which climate change will impact food systems and adaptations to future risks remains unanswered (Alexandridis et al. 2023). Women and youth’s agricultural contributions to food and nutrition are significant, as they engage in subsistence farming and small- and medium-sized enterprises as agricultural agri-entrepreneurs. However, their agricultural activities are often hindered due to unequal ownership of quality farmland and the need for more capital, technology, information, and other resources to invest in agriculture. Technological advancement continues to show the potential to improve crop yields and productivity. Nevertheless, there is a need to explore why certain underlying behavioral and socioeconomic factors continue to shape and influence innovations’ (non) adoption. The aim of this presentation is to: (i) discuss the specific mechanization technologies used by men and women across the East and Southern Africa One CGIAR Regional Integrated Initiative—Ukama Ustawi, and (ii) unpack the barriers and opportunities for the uptake of technologies by men, women, and youths for maize-mixed farming. The study followed a qualitative data-collection method with focused group discussions and key informant interviews in Kenya, Malawi, Zambia, and Zimbabwe. While the findings varied across the gender categories, they all indicated that a gender-responsive approach is needed to support technologies and innovations.